PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) UNTUK PENANGANAN KEPUTIHAN DI DESA RASAU JAYA UMUM - Etiek Nurhayat; Slamet Slamet; Herlinda Djohan (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Pathological vaginal discharge is a common health problem among women and is often caused by infection with Candida albicans. The community in Rasau Jaya Umum Village had limited access to health facilities, creating a need for alternative treatment based on family medicinal plants. This community service activity aimed to enhance the knowledge and skills of local residents in utilizing medicinal plants such as betel leaves, temulawak, galangal, and kesum leaves for preventing and managing vaginal discharge. The activity was carried out through preparation, site survey, coordination with village authorities, health education sessions, and demonstrations on the use of medicinal plants. The educational session was conducted in August 2025 and involved community members, health cadres, and posyandu cadres. The results showed an increase in community understanding regarding the use of medicinal plants as an alternative approach to managing vaginal discharge. The mandatory output in the form of electronic media publication was achieved through the release of a documentation video. This activity concluded that empowering the community through the use of family medicinal plants served as an effective and practical approach to supporting women's reproductive health